IMPLEMENTASI MANAJEMEN “RE” UNTUK MENGURANGI JAM KOSONG SERTA KETERLAMBATAN GURU DATANG DAN MASUK KELAS DI SD NEGERI 163099 - Nurmala Tampubolon (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
ABSTRACTThe purpose of writing to reduce school hours, reduce the number of teachers who are late in school, reducing the number of teachers who are late to class. The cycle pattern that the authors offer starts from the control, improvement/improvement, maintenance, action, planning, inspection and implementation. Control needs to be done on input products, process work (KBM) or PBM implementation until the end of output. Therefore, it is necessary to develop a "quality mentality mentality" attached to the processor (built in quality) and implement (do it right the first time). From the results obtained it can be conveyed here that with the management of RE can reformat teacher discipline and effect on student discipline, which finally will realize the school effective and superior. Writing is expected not only a big dreaming, but also can be done and implemented from the small (start from little) which then through the action (do it now).Keywords: Management Implimentation, RE, School Displin